Microstructures of alumina-aluminium/magnesium interpenetrating composites - Rebecca Higginson; Hong Chang; J.G.P. Binner (2006)
Interpenetrating composites allow a completely 3-dimensional matrix of two phases, in this case an alumina (ceramic) and aluminium-magnesium alloy (metal), to be developed. This 3-dimensionality yields a material with mechanical and physical properties that are superior to either the metal or ceramic individually. The composites were produced by heating an alumina foam and aluminium-magnesium alloys together in flowing nitrogen to in excess of 900°C. At these temperatures the alloy is drawn into the ceramic foam by capillary action. The infiltration process is dependent on the interaction of the alloy with the nitrogen atmosphere in the furnaces. This complex interaction and its affect on the microstructural development has been studied using Electron Backscatter Diffraction (EBSD) coupled with Energy Dispersive x-ray Spectroscopy (EDS).